Role of Social Media on Covid-19 Pandemic - M, GAJAPRIYA; ARIVARASU, LAKSHMINARAYANAN; R V, GEETHA (The journal of contemporary issues in business and government, 2020)
The 2019 novel coronavirus (2019-nCoV) is rapidly spreading and it originates from Wuhan City of Hubei Province of China which causes infectious disease Coronavirus disease (COVID-19). Most people infected with the COVID-19 will experience mild-to-moderate fever,cough,sneezing and respiratory illness with no specific treatment available. With the internet, social media have become the most acclaimed tool for freedom of speech, democracy, truth and source of infotainment. In a pandemic situation like the Covid-19 outbreak ,social media has become the most searched venue for information gathering . There are thousands of people spreading information,sensationalism, rumours ,misinformation making it crucial for Governments and experts to fight the pandemic as well as infodemic.The way people use the internet and social media is changing slowly. The speed at which information spreads on social media is unimaginable nowadays. The aim of the study is to evaluate role of social media on covid 19 pandemic to understand whether social media is diffusing real information or fake information to the public about covid 19 pandemic.A questionnaire has been prepared regarding the role of social media on covid 19 pandemic and distributed to 100 General public. The resulting data have been analysed using statistical software.More than 70% of the participants(general public ) having negative opinions on the role of social media on covid 19 pandemic .Based on the findings of the present cross sectional study, It can be concluded that most of the General public of them having a negative opinion on the social media role on covid 19 pandemic and they are aware about the impacts of fake news spreading in social media about covid 19 pandemic .The aim of the study is to evaluate the role of social media on covid 19 pandemic to understand whether social media is diffusing real information or fake information to the public about covid 19 pandemic.